A systematic review of EFL online assessment in higher education: Effectiveness, attitudes, and challenges - Amr Selim Wannas; Marwa M. AbdelMohsen (Knowledge Management & E-Learning: An International Journal)
The global pandemic caused by COVID-19 has acted as a significant driver for the adoption of online educational practices, including instruction and assessment. Given the urgent need for an alternative to traditional assessment methods during the pandemic, various studies have explored this topic across different contexts to evaluate the impact, advantages, challenges, and learners’ perspectives on online assessment. The current paper presents a systematic review that focuses on online assessment in teaching and learning English as a foreign language (EFL) in higher education. The review summarizes existing findings on the effectiveness of online assessment, student attitudes towards its use, and the challenges of online assessment. The PRISMA model was used for article screening, inclusion, and exclusion. Out of the screened articles, 19 were included in the review process. The findings indicate that online language assessment tools provide significant gains in developing various language skills and offer benefits in terms of speed, adaptability, interactivity, and learner autonomy. Nonetheless, there are notable challenges related to technology, pedagogy, and psychology that need to be addressed. To leverage the advantages of online language assessment, the review suggests approaches that can be used to address the most prominent challenges.